USE OF INNOVATIVE TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Sirojiddinova Shahribonu Sirojiddinovna; Sayfiddinova Gullola (Journal of new century innovations, 2023)
Abstract: The article presents an excursion into the methodology of teaching English. Throughout the history of mankind, many different educational methods have been developed. The main ones are considered here, their advantages and disadvantages are indicated.